Evaluation of vision screening of 5–15‐year‐old children in three Tongan schools: comparison of The Auckland Optotypes and Lea symbols. (5th September 2019) - Hamm, Lisa M; Langridge, Fiona; Black, Joanna M; Anstice, Nicola S; Vuki, Mele; Fakakovikaetau, Toakase; Grant, Cameron C; Dakin, Steven C
Abstract : Background: Comprehensive vision screening programmes for children are an important part of public health strategy, but do not exist in many countries, including Tonga. This project set out to assess: (1) the functional vision of children attending primary schools in Tonga and (2) how a new recognition acuity test (The Auckland Optotypes displayed on a tablet computer) compares to use of a standardised eye chart in this setting. Methods: Children from three Tongan primary schools were invited to participate. Acuity testing was conducted using a standardised recognition acuity chart (Lea symbols) and the tablet test displaying two formats of The Auckland Optotypes. Measures of ocular alignment, stereo acuity and non‐cycloplegic photorefraction were also taken. Results: Parents of 249 children consented to participate. One child was untestable. Only 2.8 per cent of testable children achieved visual acuity worse than 0.3 logMAR in the weaker eye. Results from the Spot Photoscreener suggested that no children had myopia or hyperopia, but that some children had astigmatism. The tablet test was practical in a community setting, and showed ±0.2 logMAR limits of agreement with the Lea symbols chart. Conclusion: The sample of children in Tongan primary schools had good functional vision. A modified version of the tablet acuity test is a promising option for vision screening in this context.